The impact of coal price fluctuations on China's economic output. Issue 24 (20th May 2016) - Ding, Zhihua; He, Lingyun; Feng, Caicai; Li, Wenbo
ABSTRACT: Due to the important role of coal in China's macroeconomic growth, the price of coal significantly influences its economic output. Employing a VAR model, a cointegration test and a state-space model of time-varying variables, this article analyses the influence of coal price fluctuations on the volume and structure of China's economic output, including both the strength and the time delay of such influence. This article further explores the corresponding relationships between coal price fluctuations and variations in the effects of these fluctuations to analyse the asymmetric influence of coal price fluctuations on China's macroeconomy. Coal price fluctuations exerted significant long-term positive effects and short-term negative effects on China's output variables, with an average delay of 11 months; they had positive effects on investment and consumption over the long term and an increasingly negative effect on imports and exports. The average delays were 9 months for investment, 6.5 months for consumption and 10 months for imports and exports. There was an asymmetric correlation between coal price fluctuations and the time-varying elasticity of their impact on GDP. The results in this study are consistent with the actual operating circumstances of the Chinese economy.